"Frozen-Ground Cartoons": Permafrost comics as an innovative tool for polar outreach, education, and engagement. (19th February 2019) - Bouchard, Frédéric; Sansoulet, Julie; Fritz, Michael; Malenfant-Lepage, Julie; Nieuwendam, Alexandre; Paquette, Michel; Rudy, Ashley C. A.; Siewert, Matthias B.; Sjöberg, Ylva; Tanski, George; Habeck, J. Otto; Harbor, Jon
Abstract: Permafrost occupies 20 million square kilometres of Earth's high-latitude and high-altitude landscapes. These regions are sensitive to climate change and human activities; hence, permafrost research is of considerable scientific and societal importance. However, the results of this research are generally not known by the general public. Communicating scientific concepts is an increasingly important task in the research world. Different ways to engage learners and incorporate narratives in teaching materials exist, yet they are generally underused. Here we report on an international scientific outreach project called "Frozen-Ground Cartoons", which aims at making permafrost science accessible and fun for students, teachers, and parents through the creation of comic strips. We present the context in which the project was initiated, as well as recent education and outreach activities. The future phases of the project primarily involve a series of augmented reality materials, such as maps, photos, videos, and 3D drawings. With this project we aim to foster understanding of permafrost research among broader audiences, inspire future permafrost researchers, and raise public and science community awareness of polar science, education, outreach, and engagement.